Penerapan Sistem Informasi Kepegawaian pada PT Mega Ceria Lestari Berbasis Web - Riyandi, Krisna; Kesuma, Dorie P. (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2026)
Employee data management at PT Mega Ceria Lestari is still carried out manually, resulting in various problems such as difficulties in retrieving archives, duplication of leave or permit applications, loss of documents, and inconsistencies in remaining leave data. These conditions lead to slow administrative processes and reduced accuracy of the information required by the company. This study aims to design and develop a Human Resource Information System (HRIS) to address these issues and improve the efficiency of employee data management. The development method employed is the Rational Unified Process (RUP), which consists of four phases: Inception, Elaboration, Construction, and Transition. Problem analysis is conducted using the PIECES Framework, while system design is carried out using Use Case Diagrams, Activity Diagrams, and Class Diagrams. The results indicate that the implemented system improves the speed of the recruitment process, facilitates the submission and monitoring of leave and permits, enhances the accuracy of punishment data recording, and supports structured digital archiving of personnel documents. Consequently, the system is proven to increase operational efficiency and data accuracy, as well as to support managerial decision-making more effectively.